Beta decay of the Tz=-2 nucleus 64Se and its descendants. (August 2019) - Rubio, B.; Aguilera, P.; Molina, F.; Agramunt, J.; Algora, A.; Guadilla, V.; Montaner-Pizá, A.; Morales, A.I.; Orrigo, S.E.A; Gelletly, W.; Blank, B.; Asher, P.; et al.
Abstract: The beta decay of the Tz=-2 nucleus 64Se has been studied in a fragmentation reaction at RIKEN-Nishina Center. 64Se is the heavies Tz=-2 nucleus that decays to bound states in the daughter nucleus and the heaviest case where the mirror reaction 64Zn(3He, t)64Ga on the Tz=+2 64Zn stable target exists and can be compared. Beta-delayed gamma and proton radiation is reported for the 64Se and 64As cases. New levels have been observed in 64As, 64Ge (N=Z), 63Ge and 63Ga. The associated T1/2 values have been obtained.